1939
DOI: 10.1021/ie50354a006
|View full text |Cite
|
Sign up to set email alerts
|

Urea-Formaldehyde Film Forming Compositions

Abstract: The reactions of urea and formaldehyde in aqueous media are briefly reviewed in order to lead up to a study of the structure of the resinous product; the discussion is substantiated by gelation experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1940
1940
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although the reaction might be looked upon as the generation of carbon dioxide in situ with its subsequent addition to the alcohol-amine system, accompanied by the elimination of the elements of water (c/. next section), the evidence suggests that the reaction proceeds in two stages (248): first, the more nucleophilic nitrogen displaces ethoxide giving ethyl alcohol plus the ethyl carbamate derivative (Eq 4a); second, cyclization takes place with elimination of another mole of ethyl alcohol (Eq 4b). Kinetic studies (526) have shown that the reaction is third order, first order in ethyl carbonate and second order in amino alcohol.…”
Section: Preparation Of Oxazolidonesmentioning
confidence: 99%
“…Although the reaction might be looked upon as the generation of carbon dioxide in situ with its subsequent addition to the alcohol-amine system, accompanied by the elimination of the elements of water (c/. next section), the evidence suggests that the reaction proceeds in two stages (248): first, the more nucleophilic nitrogen displaces ethoxide giving ethyl alcohol plus the ethyl carbamate derivative (Eq 4a); second, cyclization takes place with elimination of another mole of ethyl alcohol (Eq 4b). Kinetic studies (526) have shown that the reaction is third order, first order in ethyl carbonate and second order in amino alcohol.…”
Section: Preparation Of Oxazolidonesmentioning
confidence: 99%
“…In the past three years the butanol-etherified urea-formaldehyde resins have achieved vast industrial acceptance (1,4,6,11,12,17,25). These resins have been widely adopted as part of the vehicle of baking enamels by manu-important industrial articles, particularly when used with the nondrying and semidrying alkyd resins.…”
Section: Thementioning
confidence: 99%
“…In previous papers (11,12), the general formulation of white and colored urea-formaldehyde-alkyd resin enamels was discussed in detail. In general, the principles involving enamel formulation using accelerated urea-formaldehyde resin solutions remain substantially the same; but the effect of the accelerators in relatively small quantities cuts down the baking time from schedules such as 1 hour at 260-300°F.…”
Section: Properties Of Resin Solutions Upon Addition Of Acceleratorsmentioning
confidence: 99%